(untitled) (New York, 1993)
Economics of Aquaculture presents basic economic theory in a concise and logical format which is easily adaptable to practical application. Examples of economic solutions to common problems help you understand the need for economic application to aquaculture and the success that may come with sound economic planning and management. It also provides coverage of virtually all basic principles of microeconomics, farm management finance, and marketing applicable to the aquacultural industry. You will “walk” through the intricate maze of decisions which are necessary for success in the business environment.
Keywords: Aquaculture; Industry